Unmasking “The Great Imitator”: A Case Report of a Rare Presentation of Syphilis - Raul Marquez; Taha Shaikh; Badrunnisa Hanif (Annals of Internal Medicine: Clinical Cases)
Syphilis presents with various clinical manifestations, making diagnosis challenging. We report an atypical case involving a 58-year-old immunocompetent man with a history of penile lesions. He exhibited an ulcerated skin lesion in the right temporal region, oral condyloma, lymphadenopathy, and an abdominal wall mass. Despite inconclusive histopathologic findings of the skin lesion biopsy, a diagnosis of nonprimary syphilis was made based on strong clinical evidence, a reactive fluorescent treponemal antibody assay, and an elevated rapid plasma reagin titer. The patient showed a remarkable response to intravenous penicillin G therapy. This case report highlights the importance of early recognition and management of atypical syphilis presentations.